Syphilis situation in 20 latin american and caribbean countries: year 2006 - Galban, Enrique; Benzaken, Adele S (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: Sexually transmitted infections, especially syphilis, are found among the main causes for illnesses in the world and in the majority of Latin American countries. Objective: investigate the situation of syphilis and congenital syphilis in countries of the region and obtain an approximation of the current epidemiological situation and its tendencies. Methods: a study of transversal cut was performed and to obtain data a questionnaire was validated in the month of December of 2007 and later sent to the national program coordinators of 20 countries in the region. The implementation and information gathering period took place between January and February of 2008 and data regarding the last 4 years of the programs (from 2003 to 2007) was requested. Results: all countries have Epidemiological Surveillance services and, for the most part, total and congenital syphilis are illnesses of mandatory notification. There are at least 10 countries where congenital syphilis incidence rates are above 0,5 X 1.000 newborns, even when a high number of cases are not notified in the region. Latin America and the Caribbean notified in 2006 a percentage of total syphilis and congenital syphilis cases that is smaller than that estimated by the WHO/PAHO for the region. According to national experts and directors of national programs, the tendency of these infections in half of the countries of the region are either rising or is unknown. Conclusion: congenital syphilis continues to be a serious health problem in the region. The available information about syphilis regarding its incidence, prevalence, tendencies, intervention priorities, assistance to vulnerable groups, and availability of human and material resources is insufficient in many countries. There is opportunity to develop a collaborative work between member nations